The hedgehog effect : the secrets of building high performance teams - Vries, Manfred F. R. Kets de. (Hoboken, N.J. : Wiley, 2013)
In iThe Hedgehog Effect/i, Manfred Kets de Vries presents the case for leadership group coaching as an experiential training ground for learning to function as a high performance team. His group coaching model, incorporating living case studies, has been developed over more than 20 years of delivering programs to top-level executives and sets the standard in the field of leadership group coaching. Written for coaches, consultants, leadership development directors, and anyone working in or with teams, iThe Hedgehog Effect/i begins with an in-depth analysis of what teams and groups are all about. The intricacies of leadership coaching are illustrated with an elaborate example of a team coaching intervention. In Part Two, the author applies a psychodynamic lens to the dynamics of teams and groups, taking a close look at relationship patterns, how groups evolve, and the phenomenon of the group-as-a-whole. Part Three takes a more systemic perspective, addressing the challenges that change processes pose for people in organizations, and how to create best places to work. Kets de Vries supports the whole with the story of an organizational change initiative accomplished through group coaching.
Title from resource description page (Recorded Books, viewed November 21, 2013).
John Wiley and Sons
Keywords: Business; Affaires; BUSINESS & ECONOMICS -- Mentoring & Coaching; Business